Differential expression of VEGFA, TIE2, and ANG2 but not ADAMTS1 in rat mesenteric microvascular arteries and veins - Mecha Disassa, N; Styp-Rekowska, B; Hinz, B; Da Silva-Azevedo, L; Pries, A. R; Zakrzewicz, A (Physiological research, 2009)
Microvessels respond to metabolic stimuli (e.g. pO(2)) and hemodynamic forces (e.g. shear stress and wall stress) with structural adaptations including angiogenesis, remodeling and pruning. These responses could be mediated by differential gene expression in endothelial and smooth muscle cells. Therefore, rat mesenteric arteries and veins were excised by microsurgery, and mRNA expression of four angioadaptation-related genes was quantified by real time duplex RT-PCR in equal amounts of total RNA, correlated to two different house keeping genes (beta-actin, GAPDH). The results show higher expression of VEGFA, TIE2, and ANG2 in arteries than in veins, but equal expression of ADAMTS1. Higher availability of VEGFA mRNA in endothelial cells of arteries shown here could contribute to the maintenance of mechanically stressed blood vessels and counteract pressure-induced vasoconstriction.
Keywords: Animals; mikrocirkulace; Vasoconstriction; Receptor, TIE-2; Endothelium, Vascular; vazokonstrikce; vaskulární endoteliální růstový faktor A; Muscle, Smooth, Vascular; proteiny ADAM; Vascular Endothelial Growth Factor A; fyziologická adaptace; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; Rats, Sprague-Dawley; arteriae mesentericae; RNA, Messenger; ADAM Proteins; Mesenteric Veins; Male; Reverse Transcriptase Polymerase Chain Reaction; potkani Sprague-Dawley; svaly hladké cévní; Microcirculation; Adaptation, Physiological; Mesenteric Arteries; krysa rodu Rattus; exprese genu; cévní endotel; Angiopoietin-2; zvířata; angiopoetin-2; mužské pohlaví; vena mesenterica; receptor TIE-2; Rats; Gene Expression